Special issue “Conflicts and debates on Regional History in the current Argentina” (Quinto Sol, 2018)
This dossier contains five articles on the current status and meanings of “regional history” in Argentina, this is an expanding field of studies since the mid-eighties, mainly rooted in Argentine provinces rather than metropolitan universities. Regional historians tend to use local scale and micro-historical approach in order to discuss more consolidated historiographical interpretations on national history. The texts concentrate in two main goals: first, to show which were the most important theoretical and methodological debates among regional historians, but also with mainstream historians; second, to update the regional history research agenda attending to the impacts of the “transnational turn”.
Keywords: Regional History; Argentine Historiography.